An Insight on Gut Flora, Colorectal Cancer Mechanism, and Treatment Strategies - Rajendra Kumar; Ashmeen Kaur; Divyanshu Rajput (Advanced Gut & Microbiome Research)
The microbiota in the stomach functions like an actual organ. To maintain gut homeostasis, the digestive tract’s symbiotic relationships with the local microorganisms are crucial. This symbiotic connection may be upset, and illnesses like inflammatory bowel disorders and cancer can be promoted. Infections, dietary changes, and lifestyle modifications are a few examples of environmental factors that might alter the microbiome. It is becoming increasingly clear that the microbiota plays a part in the development of colorectal cancer. The complex interplay of tumour cells, nonneoplastic cells, and a large variety of microbes results in colorectal cancer. About 10% of new cancer cases globally are colorectal cancer instances (CRC). The gut microflora, which is situated adjacent to the colorectal epithelium, is made up of a sizable population of bacteria that interact with host cells to control a variety of physiological functions, including energy production, metabolism, and immune response. Sequencing research has revealed microbial compositional and ecological changes in CRC patients, while functional research in animal models has identified several bacteria, including Fusobacterium nucleatum, specific strains of Escherichia coli, and Bacteroides fragilis, as key players in the development of colorectal cancer. In this review, we focus on dysbiosis and the potentially carcinogenic characteristics of bacteria to evaluate the possible connections between the bacterial microbiota and colorectal carcinogenesis. We also discuss pertinent mechanisms in microbiota-related carcinogenesis, the potential for using the microbiota as CRC biomarkers, and the possibility of manipulating the microbiota for CRC prevention or treatment.